Multichannel bio-potential recording system with enhanced interference rejection capability - Dai, Fuxi (Nanyang Technological University, 2020)
Human body bio-potential signals such as Electrocardiogram (ECG) and Electroencephalogram (EEG) are critical parameters to indicate the status of human health status. Due to the inherent weak signal amplitude, bio-potential signals in human body are susceptible to the common-mode interferences coupled from the AC power line, artifacts generated by body movement or other external interference sources. Therefore, a bio-potential recording system with enhanced interference rejection capability could be a key technology that enables new applications such as remote monitoring and diagnosis for personalized home healthcare. This project presents a basic multichannel bio-potential recording circuit development with an emphasis on common mode rejection ratio (CMRR) enhancement. An ECG/EEG recording analog Front-end (AFE) system that adopts a novel Driven-Right-Leg (DRL) circuit, multichannel low noise signal amplifiers and signal filter circuits are studied, evaluated, simulated and eventually analyzed.